Exclusive Breastfeeding Practices among Female Healthcare Workers and Child Welfare Clinic Mothers in the Sissala East Municipality of Ghana - Dinwia, Jonas; Wireko, Sabina Ampon- (South Asian Journal of Social Sciences and Humanities, 2024)
Babies, mothers, and society as a whole all benefit greatly from exclusive breastfeeding. Babies who are breastfed alone are protected from harmful bacteria that can be found in formula and other infant meals, bacteria that can cause diarrhoea, other illnesses, and even death. The study investigated exclusive breastfeeding practices among female healthcare workers and child welfare clinic mothers in the Sissala East Municipality of Ghana. A facility-based quantitative descriptive cross-sectional design was used in this study. Twenty-five lactating mothers were purposively selected using a simple random technique. Data was collected using a closed-ended questionnaire and data analysis using IBM SPSS version 21.0. The results showed that mothers whose income ranged from 500 cedis to 1000 cedis were 3.29 times more likely to breastfeed exclusively compared to those whose income was not up to 500 cedis (COR:3.29 (C.I:1.11 – 9.71) P=0.031). Those in other professional groups were 43% less likely to practice exclusive breastfeeding than those who were health workers.